The changing nature of aminoglycoside resistance mechanisms and prevalence of newly recognized resistance mechanisms in Turkey - HASDEMİR GÖKBOĞA, MÜNEVVER UFUK (BLACKWELL SCIENCE LTD, 2001)
Objective, To determine the most frequently. occurring individual and combined resistance mechanisms, in Gram-negative bacteria resistant to any of the clinically available aminoglycosides in Turkey, and to compare these mechanisms with those found in smaller, earlier studies. Methods Aminoglycoside resistance mechanisms in Gram-negative isolates, resistant to either gentamicin, tobramycin, netilmicin or amikacin collected in different regions of Turkey were evaluated both phenotypically and genotypically using 12 aminoglycosides, and up to 22 aminoglycoside resistance gene probes. Results Among 696 aminoglycoside-resistant Gram-negative bacteria, resistance rates were very high for gentamicin (94.5%), tobramycin (82.4%). netilmicin (53.6%), and amikacin (49.7%). Although isepamicin was the most active aminoglycoside, against Gram-negative bacteria, increased resistance (29.7%) was found and resistance rates were higher than those in most of the other countries surveyed in earlier studies. The most common aminoglycoside resistance mechanisms (AAC(3)-II (GTN), AAC(6)-I (TNA), and ANT(2)-I (GT)) in the earlier studies were also found in the present isolates of Klebsiella spp., Enterobacter spp. and Escherichia coli, with increased complexity. In addition to these old mechanisms, two new aminoglycoside resistance mechanisms, namely AAC(6)-III (TNAI) and AAC(6)-IV (GTNA), were also found at significant frequencies (11.9% and 26.9%, respectively) in these isolates of Enterobacteriaceae (n = 435). Among the isolates of Pseudomonas spp. (n = 150), in addition to the increased complexity of enzymatic resistance mechanisms (AAC(3)-I (16.6%), AAC(6')-II (29.3%), AAC(6)-III (19.3%), ANT(2)-I (40%)), permeability resistance seemed to be responsible for the high rates of resistance to, aminoglycosides. Conclusion The results of this. study indicated increased resistance to clinically available aminoglycosides, including isepamicin, even though it was, the most active, as a result of both the presence of new aminoglycoside resistance mechanisms and the increased, complexity of all mechanisms, including permeability resistance, particularly in Pseudomonas in Turkey.
Keywords: aminoglycoside resistance mechanisms; phenotyping; genotyping; gram-negative bacteria; PSEUDOMONAS-AERUGINOSA; UNITED-STATES; GENE